Psychological distress and parent reporting on child health: The case of developmental delay. (April 2017) - Veldhuizen, Scott; Bedard, Chloe; Rodriguez, Christine; Cairney, John
Abstract: Background: Caregiver-completed screening questionnaires are a common first step in the identification of developmental delay. A caregiver's mood and anxiety level, however, may affect how he or she perceives and reports possible problems. Aims: In this article, we consider the association between caregiver distress and the accuracy of the Ages and Stages Questionnaire (ASQ), a widely-used screen. Methods and procedures: Our sample includes 857 parent-child dyads drawn from the Psychometric Assessment of the NDDS Study (PANS) and the NDDS Alternate Responses Study (NARS). Parents completed the ASQ and the K6, a brief measure of generalized distress. Children were assessed using the Bayley Scales of Infant and Child Development (BSID). We divided children on BSID result and used logistic regression to examine how distress influenced the ASQ's accuracy in each group. Results: Of our 857 children, 9% had at least one domain below −2 standard deviations on the BSID, and 17.3% had positive ASQ results. Caregiver distress predicted a positive ASQ substantially and significantly more strongly among BSID-positive children than among others. This translates into slightly reduced ASQ specificity but greatly improved sensitivity among caregivers with higher distress. Conclusions: At low to moderate levels of distress, greater distress is associated with greater ASQ accuracy.